How imagining personal future scenarios influences affect: Systematic review and meta-analysis. (February 2020) - Schubert, Torben; Eloo, Renée; Scharfen, Jana; Morina, Nexhmedin
Abstract: Imagining the future is a fundamental human capacity that occupies a large part of people's waking time and impacts their affective well-being. In this meta-analysis, we examined the effect of (1) positive future imagination and (2) negative future imagination on affect, and (3) compared the affective responses between imagining the future and remembering the past; lastly, we (4) examined potential moderating variables in this regard. We identified 63 experimental studies ( N = 6813) from different research areas and combined studies that applied the best possible self imagination task, future worry induction, and episodic future simulation, respectively. Findings yielded that imagining the future has a moderate to strong impact on affect, and it has a stronger influence on affect compared to remembering the past. Relevant moderator variables in each research area were also identified. We discuss the findings for the field of psychology in general and clinical psychology in particular. More elaborate research on personal future imagination seems crucial for the further advancement of clinical applications for mental health complaints. We conclude with recommendations for future research on the impact of future imagination on affective well-being. Highlights: Instructed positive personal future imagination boosts positive affect. Future worry increases negative affect equally in high-anxious and low-anxious individuals. Imagining the future evokes stronger affect than remembering the past. Magnitude of effects depends on how an imagination is applied. Future research needs to focus more on clinical application of future imagination.